Effect of sesame protein isolate modified by high-pressure homogenization, high-intensity ultrasound, and high-pressure processing on the colloidal stability of sesame paste: Determination of physicochemical, rheological, microstructural properties and storage stability - Gul, Osman; Sahin, Melike Seyda; Saricaoglu, Furkan Turker; Atalar, Ilyas (Elsevier BV, 2024)
In this study, sesame protein isolate modified with different emerging technologies, including high-pressure homogenization, high-intensity ultrasonication, and high-hydrostatic pressure, was applied to improve the stability of sesame paste. Sesame protein addition reduced the phase separation by up to 48% in sesame paste compared to the sample (control) without protein addition, and also significantly enhanced the firmness and spreadability. With the addition of sesame protein isolate, the sesame paste samples formed a denser and more compact appearance. The flow characteristics of samples were better fitted by the Herschel-Bulkley equation, and modifying the added protein also played an essential role in improving the flow properties of sesame paste samples. Phase separation and oxidative stability of sesame paste were significantly improved by the addition of modified protein. Overall, the results indicated that sesame protein modified with HPH technology has a significant potential to improve the quality of sesame paste and prevent phase separation.